Echographic features of the structure of atherosclerotic plaques in carotid ischemic stroke - A. Yu. Vishnyakova; A. B. Berdalin; D. A. Golovin; S. E. Lelyuk; V. G. Lelyuk (Неврология, нейропсихиатрия, психосоматика, 2020)
An assessment of not only the degree of stenosis, but also the structure of atherosclerotic plaques (ASPs) in the carotid arteries can reveal atheromas that are dangerous for the development of cerebrovascular events in asymptomatic individuals.Objective: to study the echostructure of ASPs in patients in the acutest period of carotid ischemic stroke (IS) and to analyze predictors for its development according to ultrasonic duplex scanning (DS).Patients and methods. A study group included the results of DS in 668 patients (370 men and 298 women aged  63±11 and 69±9 years, respectively) with IS in the middle cerebral artery bed. Out of 222 patients, 160 (72.1%), 56 (25.2%), 4 (1.8%), and 2 (0.9%) people had atherothrombotic, cardioembolic, hemodynamic, and lacunar subtypes of IS, respectively. A control group consisted of 903 asymptomatic individuals matched to the patients for gender and age.Results and discussion. In patients with IS, carotid stenoses were characterized by the higher degree of a reduction in the lumen of both the internal carotid arteries (ICA): on the right (r) (53±23%) and left (l) (54±24%) sides, and the common carotid arteries (CCA): on both sides (40±12%) compared to asymptomatic individuals: rICA (40±14%), lICA (39±15%); and both CCAs (32±9%). At the same time, ASPs in the carotid arteries in the acutest period of IS were significantly more frequently homogeneous hypoechoic (21.2%) or heterogeneous with a hypoechoic component (25.6%), and also more frequently had an uneven contour in the rICA (41.3%) and lICA (33.6%), compared to those in asymptomatic individuals (hypoechoicity (7.0 and 5.6%, respectively); the uneven contour was in the rICA (3.2%) and lICA (4.0%). The study indicated that a set of echo signs (the degree of stenosis in the ICA and CCA; the homogeneity and hypoechoicity of ASP in the ICA; the uneven contour of ASP in the carotid arteries) was formed for primary ultrasound carotid stenosis screening carried out using a routine DStechnique. Additional studies that can more accurately identify ASPs that are dangerous for the development of cerebral vascular events are recommended for asymptomatic individuals with ASP and the above signs, which will determine their treatment policy.Conclusion. Atheromas in the carotid arteries in the acutest period of IS are different from those in asymptomatic individuals by a number of features identified during routine ultrasonic DS. The most valuable individual prognostic sign of the development of carotid IS was the uneven contour of ASP in the carotid arteries.